Investigating the interplay between the Tup1-Cyc8 and Swi-Snf chromatin remodelling complexes in Saccharomyces cerevisiae - Byrne, Nicole (Trinity College Dublin. School of Genetics & Microbiology. Discipline of Microbiology, 2021)
Swi-Snf is an ATP dependent chromatin remodelling complex which acts as a co-activator of gene transcription by its ability to open up densely packed chromatin by removal of nucleosomes. Conversely, Tup1-Cyc8 is a co-repressor complex that has the ability to position nucleosomes at the promotors of genes, forming a more closed chromatin state which is repressive towards transcription. The antagonistic activity of these two complexes has recently been shown to regulate102 genes by RNA-Seq analysis. In this study I have validated the subset of genes suggested to be under the co-regulation of Swi-Snf and Tup1-Cyc8 using gene-specific RT-qPCR and ChIP analysis. Using ChIP analysis of Snf2 and Tup1 proteins at gene promotors, examples of some of the co-regulated genes wereshown to be under the direct control of Swi-Snf and Tup1-Cyc8. The data also revealed that at these co-regulated genes Tup1occupancywas dependent on Snf2. Furthermore, Tup1 can persist at co-regulated genes in the absence of Cyc8 and that this retention of Tup1 is Snf2dependent. Finally, the data revealed that there may be two models of co-regulation. In model one, Tup-Cyc8 occupies the promotor of target genes to bring about repression. In the absence of Tup1-Cyc8, Swi-Snf is recruited resulting in gene activation. In model two, Swi-Snf and Tup1-Cyc8 both occupy the promotors of target genes with Swi-Snf becoming further enriched upon target gene activation in the absence of Tup1-Cyc8. Moreover, preliminary data might suggest that the two complexes interact with one another via the Swi3 and Cyc8 proteins.
APPROVED